The Effect of Brand Equity on Patient Loyalty with Patient Satisfaction as a Mediating Variable in Inpatient Services - Offia Melda Permata Hartamto; Sholihul Absor2; Heru Suswojo (Jurnal Ragam Pengabdian, 2026)
Low inpatient utilization, reflected in suboptimal Bed Occupancy Rate (BOR), remains a challenge for many hospitals. Strengthening brand equity is increasingly recognized as a strategic approach to enhance patient loyalty and improve service utilization. This study aimed to examine the effect of brand equity on patient loyalty, with patient satisfaction as a mediating variable, among inpatients at RSI Siti Aisyah Madiun. This study employed a quantitative cross-sectional design involving 100 inpatient respondents selected using purposive sampling. Data were collected using a structured questionnaire measuring brand equity, patient satisfaction, and patient loyalty. Data analysis included descriptive statistics, validity and reliability testing, classical assumption tests, multiple regression analysis, and Sobel test for mediation analysis. The results showed that brand equity had a significant positive effect on patient satisfaction and patient loyalty (p < 0.05). Patient satisfaction also significantly influenced patient loyalty (p = 0.05). Mediation analysis revealed that patient satisfaction partially mediated the relationship between brand equity and patient loyalty. Brand equity plays a crucial role in strengthening patient loyalty, both directly and indirectly through patient satisfaction. Hospital management should prioritize brand-building strategies supported by consistent service quality to enhance patient satisfaction, foster loyalty, and potentially improve inpatient utilization and BOR.